Factors Influencing Smallholder Farmers Mechanization Decisions in Nigeria: The Case of Tractor Use in the Fourth Industrial Revolution ERA - Onomu, Achoja Roland; Aliber, Michael (Asian Journal of Agriculture and Rural Development, 2021)
Tractorization is crucial in the agricultural transformation of societies with either large farm size or challenged by a severe labor shortage. However, most smallholder farmers still lag in its use, making it necessary to investigate current tractor use by smallholders. This study investigated the factors that influence smallholder farmers’ decision to use tractors in the Delta and Benue States of Nigeria. Specifically, it determined the current level of mechanization (tractor use) in the farming system, estimated the contributions of tractor use among smallholder farmers, and determined the factors influencing smallholder farmers’ tractor use decisions in the study area. Multistage sampling techniques were used to collect data from 280 respondents. Descriptive statistics, a logistic model and odds ratio (OR) constituted the analytical framework. The results showed that poor tractor use still exists among smallholder farmers, with as much as 72% of farmers not using tractor in this modern era. The study revealed that the mean income of tractor users was twice as high as that of non-tractor users. The OR result revealed that educational status, household labor, farming experience, alternative occupation, and farm area under cultivation influenced the decision of the smallholder to use tractor services. It would seem that lack of utilizing the benefits of tractorization is a crucial constraint that calls attention to the need for a holistic campaign among the farming population. The practical applications of family labor are likely to remain high.